2021
DOI: 10.23876/j.krcp.20.184
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and clinicopathologic classifications of antineutrophil cytoplasmic antibody-associated glomerulonephritis: a validation study in a Korean cohort

Abstract: Background: Antineutrophil cytoplasmic antibodies (ANCA)-associated glomerulonephritis (AAGN) is a common cause of rapidly progressive glomerulonephritis and requires prompt and proper immunosuppressive therapy to improve renal prognosis. This study aimed to evaluate the predictive value of two different classifications for renal outcomes in Korean AAGN patients. Methods: Ninety-two patients who were diagnosed with AAGN at two tertiary hospitals between 2004 and 2018 were retrospectively analyzed retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…The RRS has been validated as a good prognostic tool for renal disease in Japan, Korea, Mexico, and Spain [ 5 , 6 , 12 , 13 ]. In the present study, renal prognosis deteriorated sequentially in the low, medium, and high RRS groups, which is consistent with the findings of Brix et al The present study has similar background characteristics to studies in Japan and Korea [ 14 16 ], but is in contradiction with their study, which showed a similar prognosis for the medium RRS group and the low RRS group [ 5 , 6 ]. There are several possible reasons for this inconsistency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RRS has been validated as a good prognostic tool for renal disease in Japan, Korea, Mexico, and Spain [ 5 , 6 , 12 , 13 ]. In the present study, renal prognosis deteriorated sequentially in the low, medium, and high RRS groups, which is consistent with the findings of Brix et al The present study has similar background characteristics to studies in Japan and Korea [ 14 16 ], but is in contradiction with their study, which showed a similar prognosis for the medium RRS group and the low RRS group [ 5 , 6 ]. There are several possible reasons for this inconsistency.…”
Section: Discussionmentioning
confidence: 99%
“…The renal risk score (RRS) is based on three parameters-estimated glomerular filtration rate (eGFR), percentage of normal glomeruli, and rate of renal tubular atrophy and interstitial fibrosis (TA /IF)—which are classified into three groups according to severity. There is increasing evidence that RRS plays an important role in predicting renal prognosis in ANCA-associated glomerulonephritis (AAGN) [ 4 6 ]. Chen et al reported that Birmingham Vasculitis Activity Score (BVAS) was associated with poor renal prognosis in AAGN [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated higher kidney survival rates in the order of focal, crescentic, mixed, and sclerotic classes (12). A recent study provided information on the predictive potential for kidney outcomes of both histopathological and clinicopathologic classi cations in Korean patients with AAV-GN (13). However, the study had three limitations.…”
Section: Introductionmentioning
confidence: 96%
“…* eGFR (* during follow-up(12,13). First, this may occur due to the heterogeneous nature of the focal class, which may include glomeruli with an underlying pathology that is not yet fully observable by light microscopy.…”
mentioning
confidence: 99%
“…Some studies compared the prognostic values of Berden's classification versus RRS for renal outcomes and revealed that RRS had better predictive ability than Berden's classification. However, these studies were limited to comparing discrimination ability and predicting overall survival (13)(14)(15). A more comprehensive comparison between Berden's classification and RRS are needed.…”
Section: Introductionmentioning
confidence: 99%